2000
DOI: 10.1002/1096-9098(200005)74:1<79::aid-jso17>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Current role of radiotherapy in the treatment of locally advanced laryngeal carcinomas

Abstract: The indications for combined treatment should be correlated with the prognostic factors to increase the survival rate of patients with stage III and IV laryngeal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Even though the survival rates were comparable, the combined surgery and RT group was composed of subjects with more unfavorable prognostic factors. 23 Our data show that surgery alone, RT alone, and combined surgery and RT produce equivalent results in stage IV glottic cancer.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Even though the survival rates were comparable, the combined surgery and RT group was composed of subjects with more unfavorable prognostic factors. 23 Our data show that surgery alone, RT alone, and combined surgery and RT produce equivalent results in stage IV glottic cancer.…”
Section: Discussionmentioning
confidence: 53%
“…A more recent study of a large series of stages III and IV laryngeal carcinomas compared 163 (43%) patients who underwent surgery only with 217 (57%) patients who received surgery and postoperative RT. Even though the survival rates were comparable, the combined surgery and RT group was composed of subjects with more unfavorable prognostic factors 23 . Our data show that surgery alone, RT alone, and combined surgery and RT produce equivalent results in stage IV glottic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A similar opinion was presented by Wieczorek [ 12 ]. Also Cortesina et al [ 19 ], who used ECOG performance status classification, showed no prognostic role of this parameter.…”
Section: Discussionmentioning
confidence: 99%
“…RT is often used with other treatment modalities. Postoperative RT is used in locally advanced laryngeal tumors to decrease recurrence [25]. It is also used with CT in a variety of organ preservation regimens described below [26].…”
Section: Overview Of Treatment Options For Laryngeal Cancermentioning
confidence: 99%